Penerapan Sistem Manajemen Informasi BAZNAS (SIMBA) Pada Badan Amil Zakat Nasional Kabupaten Tanah Datar - Asrida Asrida; Atika Amor; Revi Candra (ZAWA: Management of Zakat and Waqf Journal, 2021)
The purpose of this study was to determine the implementation of the Baznas Information Management System (SIMBA) at the National Amil Zakat Agency of Tanah Datar Regency. This study uses a qualitative descriptive analysis method by conducting observations and interviews. The role of Zakat Management Organizations (OPZ) is very important in optimizing the large zakat potential in Indonesia. A system built and developed for data and information storage purposes owned by BAZNAS nationally is the BAZNAS Information Management System (SIMBA). SIMBA is also equipped with a reporting printing feature which includes 88 different types of sub reports which are classified into 33 types of reports in 5 major groups. Being web-based, this system is centralized at the center so that it can be used by all zakat agencies or institutions throughout the archipelago without having to go through a complicated installation process. SIMBA also facilitates the presentation of financial reports of all zakat management activities which are summarized and presented in the Balance Sheet and other activity reports that are transparent and accountable to stakeholders and the government as a form of accountability for BAZNAS which has referred to PSAK 109. The results showed that BAZNAS Tanah District Datar has started implementing PSAK 109 through SIMBA since 2016 and has only been maximal in 2018. In its implementation, the obstacle faced by SIMBA operators is the operator's lack of understanding of zakat accounting.